Effects of growth-promoting bacteria on soybean root activity, plant development, and yield - Moretti, Luiz Gustavo [UNESP]; Crusciol, Carlos A. C. [UNESP]; Kuramae, Eiko E.; Bossolani, João W. [UNESP]; Moreira, Adônis; Costa, Nídia R. [UNESP]; Alves, Cleiton J. [UNESP]; Pascoaloto, Isabô M. [UNESP]; Rondina, Artur B. L.; Hungria, Mariangela (Wiley, 2020)
Rhizobia and other plant growth-promoting rhizobacteria (PGPR) have been broadly used as inoculants in agriculture, resulting in morphofunctional improvements in roots and grain yield. This study was carried out during two cropping seasons under field and greenhouse conditions in Brazil to verify the effects of inoculation of two soybean cultivars with PGPR and secondary microbial metabolites (SMMs) on root activity and nodulation, plant development, and grain yield. Inoculation and co-inoculation treatments consisted of Bradyrhizobium japonicum strain SEMIA 5079 and B. diazoefficiens strain SEMIA 5080 inoculated together, in combination with Bacillus subtilis strain QST 713, Azospirillum brasilense strains Ab-V5 and Ab-V6, and SMMs extracted from B. diazoefficiens strain USDA 110 and Rhizobium tropici strain CIAT 889. Root systems were evaluated by direct (optical reading) and indirect (rubidium nitrate application, 85RbNO3) methods. Increases of up to 1.6% in root diameter (0.01- to 0.5-mm class), 28.5% in length, 19.7% in root volume, 17.8% in root surface area, 29% in the number of nodules, 27.2% in nodule dry weight, 13.5% in root dry weight, and 3.8% in shoot dry weight. Greater exploration and activity within and between rows following inoculation at up to 40 and 10 cm in depth, respectively, were observed in plants co-inoculated with the standard inoculation (only Bradyrhizobium spp.) + SMMs + A. brasilense, resulting in a yield increase of 485 kg ha−1. The results emphasize the biotechnological potential of using secondary metabolites of rhizobia with inoculants containing rhizobia and PGPR to improve the growth and soybean yield in tropical conditions.